The towering intellectual - Abd Razak, Dzulkifli (2007)
He was a towering intellectual, an internationally renowned scholar and thinker. Professor Datuk Syed Hussein Alatas passed away on Jan 23 after a heart attack. He was 78. Born on Sept 17,1928 in Bogor, Indonesia, his thoughts and contributions began from his early days in universities, both in Malaysia and Singapore. He served as the fourth vicechancellor (May 1988January 1991} of University of Malaya, fully committed to the ideals of scholarship. Earlier on, Syed Hussein was thrown into the limelight for his critical comments about the declining quality of education. His last stint was at the Institute of the Malay World and Civilisation at Universiti Kebangsaan Malaysia which began in 1999.